Delegating Away Democracy: How Good Representation and Policy Successes Can Undermine Democratic Legitimacy. (November 2018) - Singer, Matthew
Theories of democratic legitimacy argue that people who believe the government is well managed and represents their interests are likely to defend the democratic status quo. Principal-agent theory predicts, however, that these same groups are also more likely to support executive actions that threaten vertical or horizontal accountability. Citizens who feel represented by an ideologically sympathetic and competent executive may be willing to delegate the president additional authority to enact their agenda, even at the expense of democratic principles. Survey data from Latin America are largely consistent with the principal-agent hypothesis; those who voted for the ruling party in the previous election or who perceive that the economy is strong say they not only like democracy and oppose coups but also support limits on critical actors and opposition parties and are willing to let the president bypass the legislature and court. Thus to understand the breakdown of democracy, we must not only examine the conditions that leave the losers of political and economic processes satisfied with the process that culminated in their defeat but also identify conditions when winners tolerate electoral and institutional challenges and are willing to protect space for public criticism.